2021
DOI: 10.1007/jhep05(2021)124
|View full text |Cite
|
Sign up to set email alerts
|

Large N gauge theories with a dense spectrum and the weak gravity conjecture

Abstract: We find large N gauge theories containing a large number of operators within a band of low conformal dimensions. One of such examples is the four-dimensional $$ \mathcal{N} $$ N = 1 supersymmetric SU(N) gauge theory with one adjoint and a pair of fundamental/anti-fundamental chiral multiplets. This theory flows to a superconformal theory in the infrared upon a superpotential coupling with gauge singlets. The gap in the low-lying spectrum scales as 1/N and the central charges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…In fact, it has been argued in [6], that this is one of the necessary conditions for a CFT to be holographic. In [7], two of the authors of the current paper showed that there exists a rather unconventional large N gauge theory. It is a simple 4d N = 1 supersymmetric SU(N ) gauge theory with an adjoint and a pair of fundamental and anti-fundamental chiral multiplets.…”
Section: Jhep10(2021)049mentioning
confidence: 82%
See 4 more Smart Citations
“…In fact, it has been argued in [6], that this is one of the necessary conditions for a CFT to be holographic. In [7], two of the authors of the current paper showed that there exists a rather unconventional large N gauge theory. It is a simple 4d N = 1 supersymmetric SU(N ) gauge theory with an adjoint and a pair of fundamental and anti-fundamental chiral multiplets.…”
Section: Jhep10(2021)049mentioning
confidence: 82%
“…N f = 1 theory. The N f = 1 case was already studied in [7]. We repeat the same analysis here with a slightly refined analysis of the Weak Gravity Conjecture.…”
Section: Jhep10(2021)049mentioning
confidence: 85%
See 3 more Smart Citations